Reconstituting Pedagogical Authority in the GenAI Era: Intelligent-TPACK, Deep Learning, and the Ethical-Cultural Knowledge of Maja Labo Dahu in Islamic Religious Education - Lalu Muttaqin; Nasaruddin Nasaruddin; Syarifuddin Syarifuddin (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2026)
The diffusion of generative artificial intelligence (GenAI) into classrooms has produced inverted authority, a structural gap in which students' digital fluency outpaces teachers' technical mastery, placing particular pressure on Islamic Religious Education (IRE), where the teacher conventionally serves as the primary interpretive authority. No existing framework integrates AI-enabled teaching competence, deep-learning pedagogy, and culturally grounded moral resilience into a single coherent model. This qualitative case study examined how eleven IRE teachers at MAN 2 Kota Bima (West Nusa Tenggara, Indonesia) negotiate these pressures through the Mbojo philosophy of Maja Labo Dahu. Following critical-case logic, data were collected via semi-structured interviews, non-participant classroom observation (24 sessions), and an open-ended student survey (n = 93; January–March 2026), and analysed using the Miles–Huberman–Saldaña interactive model. Three findings emerged: pedagogical authority is reconstituted through reverse mentoring grounded in tawāḍuʿ (humility), confirmed across 14 of 24 observed sessions; deep-learning pedagogy is operationalised through a "language of technological analogy" mapping sharīʿah concepts onto digital metaphors, and embedded within a "Digital Compassion Protocol" aligned with Indonesia's Love-Based Curriculum (KMA 1503/2025); and Maja Labo Dahu functions as a dual self-regulation mechanism dahu (divine monitoring) and Maja (social filtering) governing student digital behaviour beyond institutional perimeters, independently recalled by 53 of 93 respondents. These findings yield the Intelligent-TPACK-Mbojo model, which extends Intelligent-TPACK by adding an Ethical-Cultural Knowledge (ECK) layer derived from community-internalized, multigenerational values rather than universal ethical principles. Counter-evidence and conditions for cross-cultural ECK substitutability are addressed explicitly.